VD_FINDINFO Jug / 2012 / 250 vom 10. Juni 2012 - VD Tribunal cantonal (2012)
DÉTENTION PRÉVENTIVE, PROPORTIONNALITÉ | 107 CP, 51 CP, 29 al. 2 Cst., 20 TFJP, 221 CPP (CH), 222 CPP (CH), 229 al. 3 let. b CPP (CH), 237 CPP (CH), 385 CPP (CH), 393 CPP (CH), 396 CPP (CH)